1093. Single Molecule Counting Technology for Ultrasensitive Quantification of Clostridium difficile Toxins A and B. (26th November 2018) - Katzenbach, Phoebe; Dave, Gipshu; Mukherjee, Ali; Todd, John; Bishop, Jeffrey; Sandlund, Johanna; Estis, Joel
Abstract: Background: Clostridium difficile, a spore-forming, anaerobic, Gram-positive bacterium, is the leading cause of nosocomial diarrhea. C. difficile infection (CDI) is mediated by two toxins, A (TcdA) and B (TcdB), and the role of each toxin in CDI pathogenesis remains unclear. Many assays used in CDI diagnostics, such as most NAATs and cell cytotoxicity neutralization assay (CCNA), detect presence of only tcdB or TcdB. In this study, an ultrasensitive immunoassay (UIA) powered by Single Molecule Counting technology was used for quantification of TcdA and TcdB, to assess toxin dynamics in CDI. Methods: Banked samples from 46 patients with suspected CDI were tested with PCR (BD MAX™ Cdiff Assay) and CCNA, and TcdA and TcdB were quantified using the UIA (tested in triplicate). The limits of detection (LoDs) for the TcdA and TcdB assays are 0.04 and 0.12 pg/mL, respectively. Results: There were 21 PCR+/CCNA+ and 25 PCR−/CCNA− samples. Both toxins were measured above LoD in all PCR+/CCNA+ samples, ranging up to 100, 000 pg/mL. The average CV for the PCR+/CCNA+ samples was 9%. The median TcdA concentrations in PCR−/CCNA− and PCR+/CCNA+ samples were 0.19 pg/mL (IQR 0.12–0.67) and 3, 301 pg/mL (125–8, 737), respectively. The median TcdB concentrations in PCR−/CCNA− and PCR+/CCNA+ samples were 0.12 pg/mL (0.12–0.21) and 2, 690 pg/mL (145–30, 307), respectively. In the PCR+/CCNA+ samples, TcdA was one or more logs higher than TcdB in two samples, one or more logs lower than TcdB in six samples, and within one log of TcdB in 13 samples. In one sample (4.8% of PCR+/CCNA+ samples), TcdA was at moderately high concentration while TcdB was below a provisional cutoff, indicating that only TcdA was expressed. There was a significant correlation between TcdA and TcdB (Spearman r = 0.753). Conclusion: The UIA allows for toxin quantification over a concentration range of ≥5 logs, suggesting that the quantitative TcdA and TcdB assays could be of value in CDI characterization and clinical decision making. The TcdA/TcdB ratio varied, and toxin quantification could be a useful tool in further understanding their individual roles in CDI. The TcdA concentration was not lower than TcdB (trended higher), indicating that detection of tcdB or TcdB alone may not be sufficient for accurate CDI diagnostics. Disclosures: P. Katzenbach, Singulex, Inc.: Employee, Salary. G. Dave, Singulex, Inc.: Employee, Salary. A. Mukherjee, Singulex, Inc.: Employee, Salary. J. Todd, Singulex, Inc.: Employee, Salary. J. Bishop, Singulex, Inc.: Employee, Salary. J. Sandlund, Singulex, Inc.: Employee, Salary. J. Estis, Singulex, Inc.: Employee, Salary.